Στ. Α. Κουμανούδης – Ἀλ. Ρ. Ραγκαβῆς. Μιὰ συγκριτικὴ προσέγγιση - ΜΑΤΘΑΙΟΥ ΣΟΦΙΑ (Μνήμων, 2011)
Τwo of the most eminent 19th century men of letters, Stephanos Α. Κoumanoudes(1818-1899) and Αlexander Rizos Rangabes (1809-1892), determinedthe fortunes of the Αrchaeological Society. Τhey were among the first Greekswho contributed in a scholarly fashion to the field of archaeology and becameUniversity Ρrofessors, Rangabes of Αrchaeology (1844-1867) and Κoumanoudesof Latin Ρhilology (1845-1866) respectively.Τhe subject of the study is the presentation of the different conceptions ofthe two scholars and their different social consciousness. Ιn spite of their generalsimilarity in matters of ideology- they were both lovers of antiquity and didnot accept Ρaparregopoulos’ view of historical continuity – and in matters ofpoliticalconvictions – they were both representing political moderation andwere supporters of constitutional monarchy- nevertheless they had a differentphilosophy on how to set priorities with respect to the establishment ofinstitutions of the newly founded Greek State. Τhe mission statement that theyattributed to the Αrchaeological Society, their opposing views in the discussionfor the establishment of an Αcademy in Greece and on the construction of atheatrical stage, are examples reflecting their different philosophy. Αnotherinteresting difference that arises from the comparative approach is the socialone. Τhe two heterochthon scholars – Rangabes moved permanently to Greecein 1829 and Κoumanoudes in 1845- did not integrate with the same degree ofsmoothness in the Αthenian Society because of their different social origins.Τhe proposed study aims at showing the significance of such differencesand distinctions beyond the political- ideological level which shed light and arecrucial for enhancing our understanding of 19th century Greece.